Enhancing the Science, Technical and Vocational Skills of Universal Basic Education Graduates in Nigeria - Dike, Joseph Egbezor; Otunne, Ray Nwakuche; Echendu, Peter C. (Mediterranean Journal of Social Sciences, 2012)
The main focus of this paper is on how acquisition of science, technical and vocational skills by theuniversal Basic Education graduates in Nigeria can be enhanced. The paper outlines how science andtechnical skills can be taught and imparted practically to the learners in the workshops and laboratories.The need to incorporate indigenous Artisans and skilled personnels into the UBE programme washighlighted. Anticipated obstacles associated with the idea of using indigenous skilled personnel was alsoexplained. Finally the paper concludes that the present universal Basic Education programme can bestrengthened and the vocational goals of the learners achieved, if the skills and expertise of the indigenouspeople are incorporated into the system. Recommendations made include, adopting a compulsory one-yearvocational skill training for all junior secondary school graduates in Nigeria.